Research on Beneficiation of a Phosphate Ore in Hubei Province - Jianguo Wang; Lijun Zhou; Hongjian Li (Kuangchan zonghe liyong, 2023)
This is an essay in the field of mineral processing engineering. Contamination of MgO and R2O3 emanating from dolomite and silicate in phosphate ore from Guizhou province has been a problem in phosphate ore processing. This study explored Scrubbing classification- Optoelectronic beneficiation- froth flotation to remove dolomite and silicate away from this phosphate ore. The phosphate minerals could be concentrated to 33.52% P2O5, with a recovery of 95.69%, and the content of MgO reduced to 0.82%, the content of Fe2O3+Al2O3 reduced to 2.84%. Additionally, scrubbing classification and photoelectric beneficiation can obtain qualified concentrate with a yield of 72.88%, which can greatly reduce the amount of ore entering the flotation operation and reduce the beneficiation cost.